KONSEP KORUPSI MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Ahmad Syarbaini (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Corruption comes from the Latin coruptio and corruptuswhich means to bribe and corrumpere which means todestroy. Corruption is included in jarîmah. Jarîmah is: